2019
DOI: 10.1103/physrevlett.123.055101
|View full text |Cite
|
Sign up to set email alerts
|

Building a Weakly Outgassing Comet from a Generalized Ohm’s Law

Abstract: When a weakly outgassing comet is sufficiently close to the Sun, the formation of an ionized coma results in solar wind mass loading and magnetic field draping around its nucleus. Using a 3D fully kinetic approach, we distill the components of a generalized Ohm's law and the effective electron equation of state directly from the self-consistently simulated electron dynamics and identify the driving physics in the various regions of the cometary plasma environment. Using the example of space plasmas, in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…The influence of the ambipolar electric potential, associated to the cometary plasma inhomogeneities and localized around the comet nucleus, in terms of particle trapping, might facilitate the electron cooling. This hypothesis shall be investigate in further details from global modeling (Deca et al 2017(Deca et al , 2019Sishtla et al 2019) to investigate the physical processes at the origin of the cold electron population far from perihelion reported in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The influence of the ambipolar electric potential, associated to the cometary plasma inhomogeneities and localized around the comet nucleus, in terms of particle trapping, might facilitate the electron cooling. This hypothesis shall be investigate in further details from global modeling (Deca et al 2017(Deca et al , 2019Sishtla et al 2019) to investigate the physical processes at the origin of the cold electron population far from perihelion reported in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Second, from March 2016 to the end of the operations when the outgassing activity was low, no electron-neutral collisions were expected despite the fact that the spacecraft was getting closer to the nucleus. Therefore, the observation of cold electrons by RPC-MIP at the end of the Rosetta cometary operations is not consistent with the cooling of newborn electrons that are ballistically escaping the inner coma region, but is rather consistent with electron that would stay longer in the denser inner cometary atmosphere region, and therefore with electrons that got trapped in the inner coma by the ambipolar electric field as shown in recent kinetic simulations of cometary electron dynamics (Deca et al 2017(Deca et al , 2019Sishtla et al 2019). In this appendix, we explain how the main resonances are extracted from the acquired RPC-MIP mutual impedance spectra (i) when the spectrum is shaped by a single resonance (Fig.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Second, in order to assess the influence of the electron acceleration processes reported in previous studies that were shown to be associated with the action of the ambipolar electric field that in turn is associated with the large-scale electron pressure inhomogeneity in the cometary ionosphere (Madanian et al 2016;Deca et al 2017Deca et al , 2019, we have used recent numerical simulations of the collisionless interaction of the solar wind with a comet to investigate the expected behavior of the electron temperature in the close cometary environment. The numerical simulation is described in Deca et al (2019) and was performed using a full kinetic particle-in-cell simulator that enabled the authors to model the kinetic behavior of electrons. This model is collisionless, so that electron cooling is not included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…An example of small-scale global, electromagnetic implicit PIC modelling for a weak comet has been performed by Deca et al (2017Deca et al ( , 2019 with a reduced proton-electron mass ratio of 100, and local simulations for a lunar minimagnetosphere (Deca et al, 2015) with a reduced proton-electron mass ratio of 256. GEM challenge, concluding that reconnection rates are well captured by smaller mass ratios of m p /m e = 180, although with modified electron kinetics.…”
Section: Introductionmentioning
confidence: 99%